A Family of Heterobimetallic Cubes Shows Spin‐Crossover Behaviour Near Room Temperature. Issue 41 (6th September 2021) - Hardy, Matthias; Tessarolo, Jacopo; Holstein, Julian J.; Struch, Niklas; Wagner, Norbert; Weisbarth, Ralf; Engeser, Marianne; Beck, Johannes; Horiuchi, Shinnosuke; Clever, Guido H.; Lützen, Arne
Abstract: Using 4‐(4′‐pyridyl)aniline as a simple organic building block in combination with three different aldehyde components together with metal(II) salts gave three different Fe8 Pt6 ‐cubes and their corresponding Zn8 Pt6 analogues by employing the subcomponent self‐assembly approach. Whereas the use of zinc(II) salts gave rise to diamagnetic cages, iron(II) salts yielded metallosupramolecular cages that show spin‐crossover behaviour in solution. The spin‐transition temperature T 1/2 depends on the incorporated aldehyde component, giving a construction kit for the deliberate synthesis of spin‐crossover compounds with tailored transition properties. Incorporation of 4‐thiazolecarbaldehyde or N ‐methyl‐2‐imidazole‐carbaldehyde yielded cages that undergo spin‐crossover around room temperature whereas the cage obtained using 1 H ‐4‐imidazolecarbaldehyde shows a spin‐transition at low temperatures. Three new structures were characterized by synchrotron X‐ray diffraction and all structures were characterized by mass spectrometry, NMR and UV/Vis spectroscopy. Abstract : Starting from simple building blocks, six heterobimetallic cubes were obtained, following a straight‐forward subcomponent self‐assembly strategy. Three iron(II) based cages showed spin‐crossover behaviour in solution. The crossover temperature was strongly dependent on interchangeable aldehyde components, giving rise to an efficient toolkit to manipulate magnetic behaviour.